Insight into bacterial biofilm-barnacle larvae interactions for environmentally benign antifouling strategies. (April 2020) - Rajitha, K.; Nancharaiah, Y.V.; Venugopalan, V.P.
Abstract: Colonization of submerged surfaces by marine organisms such as microorganisms and barnacles entails significant operational and economic problems in shipping, aquaculture, power plant cooling water systems and various other activities. Microorganisms rapidly colonize the surfaces that are submerged in seawater and form complex heterogeneous 3-dimensional structures called biofilms. These marine biofilms can interfere in the subsequent settlement of larvae of fouling organisms and biofouling process. Barnacles are the most notorious biofouling organisms for colonizing underwater structures and plaguing maritime installations. This article covers recent advances on marine biofilms, chemical signalling systems, biofilm-barnacle larval interactions, antifouling technologies and future studies for developing prospective eco-friendly antifouling strategies. Accumulating evidence indicates that marine biofilms and their chemical constituents interfere in larval recruitment for settlement or repell, thereby either promoting or deterring barnacle biofouling. Though several studies reported inhibition of barnacle larval settlement in the presence of biofilms and their exudates, characterization and identification of the chemical cues are fundamental for developing new eco-friendly antifouling strategies. Future research should be focused on better understanding of the chemistry of biofilm-associated cues that inhibit settlement of barnacle larvae as the first step and further in situ testing shall be conducted in the relevant conditions for performance evaluation to guide field applications. The knowledge accrued from biofilm-barnacle larval interactions and identification of chemical cues could possibly offer advances for prospective environmentally-benign antifouling strategies. Highlights: Biofilm formation and barnacle larval settlement are interlinked. Biofilm formation, barnacle settlement and interactions are covered. Biofilm-associated cues responsible for larval settlement are presented. Novel antifouling strategies for biofouling prevention.